The evolution of China’s policies on marine and coastal ecosystems in climate change adaptation - Bai, Jiayu; Li, Xiaoyu (Frontiers in Marine Science, 2023)
Marine and coastal ecosystems play a crucial role in adjusting the process of climate change. Mitigation and adaptation activities involve interdependent carbon and water cycles. Excessive carbon emissions burden the carbon storage capacity of the ocean and then affect the balance and stability of marine ecosystems, leading to global ocean issues such as ocean acidification and the calcification of marine life. While many studies have been conducted on this issue, there is a lack of policy analysis on how countries deal with climate change, particularly in the area of marine and coastal ecosystems’ policies. In 1992, China ratified the United Nations Framework Convention on Climate Change, and China actively participated in the governance of marine and coastal ecosystems adapting to climate change. This article reviews and textually analyses China’s policies related to the adaptation of marine and coastal ecosystems to climate change in 1992–2023. It adopts policy-oriented jurisprudence to illustrate natural and social factors which drive the evolution of China’s policies on marine and coastal ecosystems in climate change adaptation. To achieve the optimal policy results, this article recommends further enhancing the mechanism of policy implementation and management, innovating the system of policy incentives and supervision, and optimizing the framework of policy effectiveness evaluation on the basis of further policy goals.